2004
DOI: 10.1186/1471-2369-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremic hypertensive syndrome (HHS) in an 18-month old-child presenting as malignant hypertension: a case report

Abstract: BackgroundThe combination of hyponatremia and renovascular hypertension is called hyponatremic hypertensive syndrome (HHS). Malignant hypertension as a presentation has been reported in adults with HHS but is rare in children.Case presentationAn eighteen month-old male presented with drowsiness, sudden onset status epilepticus and blood pressure of 210/160. The electrolytes on admission revealed sodium of 120 mEq/L and potassium of 2.1 mEq/L. The peripheral renin activity (PRA) was 172 ng/ml/min (normal 3–11 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…We hypothesized that the symptoms of HHS would develop in children only when the stenosis in the affected artery became so severe that revascularization by PTRA was impossible. In the literature, only seven case reports of pediatric HHS with renovascular hypertension were found [2,5,6,9,10,16]. Of the nine reported cases, including the present two, PTRA was technically successful in only one case [10].…”
Section: Discussionmentioning
confidence: 52%
“…We hypothesized that the symptoms of HHS would develop in children only when the stenosis in the affected artery became so severe that revascularization by PTRA was impossible. In the literature, only seven case reports of pediatric HHS with renovascular hypertension were found [2,5,6,9,10,16]. Of the nine reported cases, including the present two, PTRA was technically successful in only one case [10].…”
Section: Discussionmentioning
confidence: 52%
“…Although initially considered a rare condition, HHS has been identified in approximately 16% of adults with unilateral renal artery stenosis [4,10]. Data on the pediatric population are still sparse [5][6][7][8][9][10][11]. In an editorial commentary, Nicholls [2] suggested that HHS may be underdiagnosed in children and probably more common than previously thought.…”
Section: Discussionmentioning
confidence: 95%
“…All presented with severe hypertension, thirst, polyuria, weight loss, confusion, and hyponatremia. HHS has been described in children as well [5][6][7][8][9][10][11][12][13], starting with the report of Blanc et al [5] in 1991. Laboratory findings of elevated plasma levels of renin in most cases suggest that the stimulation of renin release from the ischemic kidney plays an important pathophysiologic role.…”
Section: Introductionmentioning
confidence: 95%
“…Initial, safe control of blood pressure requires recognition that volume depletion may be severe (a large fall in arterial pressure with assumption of upright posture should give a clue) and activity of the renin-angiotensin system is high (as suggested by hyponatremia). Under these circumstances a vigorous and potentially dangerous fall in blood pressure has been observed in adults [32,33] and a child [19] with the first dose of an angiotensinconverting enzyme (ACE) inhibitor. Indeed, where volume depletion is severe, cautious volume repletion with intravenous isotonic saline can, as in clinical and experimental malignant hypertension [34,35], reduce arterial pressure (presumably through suppression of the activated reninangiotensin system) after which an ACE inhibitor or angiotensin receptor blocker can more safely be administered [36].…”
Section: Managementmentioning
confidence: 99%
“…Vomiting is common and could contribute considerably to the electrolyte disturbances whilst exacerbating volume depletion. In children and neonates, presenting features are polydipsia, polyuria or enuresis, weight loss and volume depletion, drowsiness, and, as in adults, various neurological and behavioral signs and symptoms [7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Clinical Featuresmentioning
confidence: 99%